Biochemical properties of different agricultural wastes treated with Pleurotus ostreatus - Sinha, Ajoy Kumar; Mehta, Rahul (Mushroom Research, 2015)
An analytical study ofÂ  different agricultural wastes namely, wheat straw, paddy straw, cotton waste, sugarcane baggasse and banana leaves was performed which included analysis of crude protein (%), crude nitrogen (%), crude fiber (%) and ash contents. These contents were estimated in all the substrates, to make the comparisons that how the cultivation of Pleurotus ostreatus led to enhancement of its contents. The mean values of the contents were noted before and after inoculation with the Pleurotus ostreatus spawn. The mean values of the ash content were found to be the maximum in cotton waste and least in banana leaves. Similarly in case of nitrogen, the mean values is found maximum in cotton waste followed by wheat straw. The highest protein content (%) was found in cotton waste followed by wheat straw, banana leaves, paddy straw and least content was in sugarcane baggasse. The mean values for the crude fiber is found maximum in cotton waste followed by sugarcane baggase, wheat straw, paddy straw and the least amount is in banana leaves. The analysis of the substrate showed the enhancement of their nutritional values.